Penerapan Total Quality Manajemen (TQM) Model Teamwork Untuk Meningkatkan Pencapaian Quality Assurancce (QA) Di SMPS IT Darul Fikri Arga Makmur - Ida Royani (Jurnal Georafflesia: Artikel Ilmiah Pendidikan Geografi, 2017)
This study aims to improve the Achievement of Quality Assurance (QA) in SMPS IT Darul Fikri Arga Makmur so that schools can deliver students to QA. To achieve this goal, researchers apply Total Quality Management (TQM) Teamwork model. In conducting this research, researchers conducted a School Action Research (PTS) using a procedure developed by Kemmis and Togart consisting of planning, execution, observation and evaluation repeatedly.The results of this study succeeded well, there has been an increase in the percentage of QA achievement starting from 60 %, increased to 65% and last 73%, although not yet achieved ideal conditions of success of 85% .In particular, the success was due to 1) the seriousness to take corrective action against the results obtained, and 2) cooperation of all parties (management, and learners). Thus the implementation of TQM Teamwork techniques can be recommended to achieve Quality Assurance (QA) in SMPIT Darul Fikri Arga Makmur can be implemented in schools that have Quality Assurance (QA).